Light Control of Salt-Induced Proline Accumulation Is Mediated by ELONGATED HYPOCOTYL 5 in Arabidopsis - Kovács, Hajnalka; Aleksza, Dávid; Baba, Abu Imran; Hajdu, Anita; Király, Anna Mária; Zsigmond, Laura; Tóth, Szilvia Z.; Kozma-Bognár, László; Szabados, László (Frontiers in Plant Science, 2019)
Plants have to adapt their metabolism to constantly changing environmental conditions, among which the availability of light and water is crucial in determining growth and development. Proline accumulation is one of the sensitive metabolic responses to extreme conditions; it is triggered by salinity or drought and is regulated by light. Here we show that red and blue but not far-red light is essential for salt-induced proline accumulation, upregulation of Δ1-PYRROLINE-5-CARBOXYLATE SYNTHASE 1 (P5CS1) and downregulation of PROLINE DEHYDROGENASE 1 (PDH1) genes, which control proline biosynthetic and catabolic pathways, respectively. ChIP and EMSA assays demonstrated that the transcription factor ELONGATED HYPOCOTYL 5 (HY5) binds to G-box and C-box elements of P5CS1 and a C-box motif of PDH1. Salt-induced proline accumulation and P5CS1 expression were reduced in the hy5hyh double mutant, suggesting that HY5 promotes proline biosynthesis through connecting light and stress signals. Our results improve our understanding on interactions between stress and light signals, confirming HY5 as a key regulator in proline metabolism.